EVALUASI EFEKTIVITAS PELAYANAN PUBLIK DI KECAMATAN KALIWUNGU SELATAN - Mashur Ali fadly; Reni Windiani; Yuwanto . (Journal of Politic and Government Studies, 2014)
ABSTRACTThis study was conducted to describe the evaluation of the effectiveness of the public service division of the District after the District of South Kaliwungu Kaliwungu. The purpose ofthis program is to increase the expansion of public services to the community as well as the close relationship between the people and the Government.In order to explain the evaluation of the effectiveness of the public service division of the District Subdistrict Kaliwungu after South Kaliwungu , then used a qualitative research method .Subjects in this study is the government represented by the Regional Secretariat of Governance Section , Southern District Government and society Kaliwungu Kaliwungu south. The datacollection method is through interview , observation , research and documents .Evaluation of the effectiveness of the District Kaliwungu expansion can be seen from several factors , namely the incumbent initiative kendal hendy boedoro to split the sub Kaliwungu which later became the Government's program to unzip the District Kendal Kaliwungu the District Kaliwungu and South Kaliwungu . District of expansion and aims to improve public services closer to the community . But the reality is happening in the field of infrastructure readiness office building becomes a major obstacle in the obstacle in providing public services to the community Kaliwungu south in particular.